Perencanaan Dan Perancangan Pusat Kreatif Masyarakat â€œKlungkung Creative Centerâ€ Di Kabupaten Klungkung: Bahasa Indonesia - I Kadek Udayana; I Putu Hartawan; I Ketut Sugihantara (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Poverty and unemployment in Bali, especially in Klungkung Regency, have experienced a significant increase over the past three years due to the Covid-19 pandemic. The poverty rate in Bali increased from 3.61% in 2019 to 4.72% in 2021, while the unemployment rate in Klungkung increased from 1.57% in 2019 to 5.37% in 2021, making it the fifth highest region with unemployment in Bali. To address the issue of unemployment and poverty in Klungkung Regency, it is necessary to build facilities that can help develop the creative industry and advance the economy. Therefore, a community creative center called